Hubungan Tingkat Pengetahuan Dan Sikap Ibu Pasangan Usia Subur (PUS) Terhadap Penggunaan Alat Kontrasepsi Di Desa Rambung Sialang Hilir Tahun 2021 - Nilawarasati; Retno Wahyuni; Tetti Seriati Situmorang; Eva Ratna Dewi (Pusat riset dan Inovasi Nasional, 2022)
Background: Family Planning (KB) is a program to balance the needs and population. Contraceptives are tools used to regulate pregnancy distance and control birth. Total Fertality Rate (TFR) in 2018 has not reached the national target of 2.31 children per woman. Knowledge and attitude of the female age couple influences in the use of contraceptives. Goals: To find out the level of knowledge and attitude towards the use of Contraceptives. Methods: This research uses analytic descriptive method with cross-sectional design, Data was collected through interview using questionnaire on 100 respondents. The analysis was conducted in univariate analysis and bivariate analysis with chi-square test with a significance level of 90% to see the relationship between the dependent and independent variables. Result: the level of knowledge and attitude of respondents in a good category, chi-square test results show a significant relation (p = 0.001) between the level of knowledge to the use of contraceptives. The relationship of attitudes towards the use of contraceptives has a significant relation (p=0.000). Conclusion: there is a significant relation between the level of knowledge and attitude of female age couple towards the use of contraceptives.